2017
DOI: 10.7589/2016-08-199
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Isolation, and Phylogenetic Analysis of Clostridium perfringens Type A and Type C from Wild Boar (Sus scrofa) in the People's Republic of China

Abstract: Clostridium perfringens is a Gram-positive, anaerobic, spore-forming bacterium that can induces gas gangrene or enteritis in poultry and humans and many other mammalian species. Here, we report an outbreak of C. perfringens type A and type C coinfection in wild boars ( Sus scrofa ). In February 2016, 10 dead wild boars, including two fresh carcasses, were found in Zhaosu County, Xinjiang Province, People's Republic of China. The two fresh carcasses were included in this study. Two strains of C. perfringens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…C. perfringens type A and type C was successfully isolated from the collected intestine samples. Authors indicated that wild boars could be a natural vector of this microorganism [48]. Our study indicated the most frequent prevalence of C. perfringens isolated from honey in the East Kazakhstan.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…C. perfringens type A and type C was successfully isolated from the collected intestine samples. Authors indicated that wild boars could be a natural vector of this microorganism [48]. Our study indicated the most frequent prevalence of C. perfringens isolated from honey in the East Kazakhstan.…”
Section: Discussionmentioning
confidence: 53%
“…However, isolates were able to produce only α toxin and any other virulence factors had not detected [47]. Another outbreak, concerning C. perfringens as a causative agent of toxemia in wild boar was reported in Zhaosu County, Xinjiang Province, PRC, near the border with Kazakhstan (East Kazakhstan region) [48]. C. perfringens type A and type C was successfully isolated from the collected intestine samples.…”
Section: Discussionmentioning
confidence: 99%
“…In an outbreak occurring in wild boar in China, C. perfringens type A and C were isolated by serological and molecular assays, and found to be the cause of death. Gross lesions consisted of extensive hemorrhage in lungs, intestine, and inguinal lymph nodes (Li et al, 2017). Hemorrhagic enteritis associated with C. perfringens type A has also been reported in a research and breeding center for pygmy hog in Assam, India.…”
Section: Bacteriamentioning
confidence: 84%
“…The pathogenesis of C. perfringens type A in pigs is poorly understood but it is likely to be multifactorial. C. perfringens is a known cause of enteritis in a variety of wild animal species and has been reported in wild suidae, such as wild boar and pygmy hogs (Das et al, 2008;Glenn Songer and Uzal, 2005;Li et al, 2017;Shome et al, 2010). In an outbreak occurring in wild boar in China, C. perfringens type A and C were isolated by serological and molecular assays, and found to be the cause of death.…”
Section: Bacteriamentioning
confidence: 99%
“…In livestock and poultry, it can cause hemorrhagic bowel syndrome and enterotoxaemia in ruminants [3], hemorrhagic gastroenteritis in dogs and horses [4], and necrotic enteritis in poultry [5,6]. In recent years, many cases of hemorrhagic enteritis caused by C. perfringens have also been reported in wild animals, especially in Chinese Milu (Père David's deer, Elaphurus davidiensis) [7][8][9][10][11]. Furthermore, hemorrhagic enteritis is characterized by acute onset, short course, and high fatality rate [9].…”
Section: Introductionmentioning
confidence: 99%